The Role of Derivation in Word Development - Abdul Hafidz bin Zaid; Hasya An’Umillah Lathifah (Universitas Pahlawan Tuanku Tambusai, 2022)
Derivation is a process in the formation of words or increasing vocabulary. Arabic language is among such languanges which are rich and prominent in this linguistic quality. The conclusion from this article is the structure of Arabic based on the derivation of letters consisting of fa’ fiil, ‘ain fiil, and lam fiil. From one derivation can give the several different word and shows different meanings, it can be concluded that derivation is necessary and important in the development of Arabic and the structure of the words. In this article the author’s using the method descriptive-analysis to examine the role of derivation in the formation Arabic Word.